Shorebirds Expert Network Monitoring Plan. Monitoring Arctic-nesting Shorebirds: An International Vision for the Future. Conclusions from The Pan-Arctic Shorebird/Wader Monitoring and Research Workshop, Denmark, 3-6 December 2003. - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (2004)
The Committee for Holarctic Shorebird Monitoring, CHASM, is a “project” within the International Wader Study Group and is one of the Expert Monitoring Networks of the Circumpolar Biodiversity Monitoring Program of CAFF. CHASM was formed as the essential first step for guiding the implementation of an effective circumpolar program for monitoring Arctic-nesting shorebirds. A circumpolar monitoring program will help ensure that existing monitoring programs continue to be well coordinated and supported, while simultaneously integrating them into a Holarctic program.